Selecting Minimum Acceptable Student’s Mark to Participate in Bologna Final Exam Using Machine Learning Approach - Ghassan Akram Qattan; Mardin Abdullah Anwer; Abbas Mohamad Ali (Zanco Journal of Pure and Applied Sciences, 2023)
In the higher education sector, the minimum acceptable mark for participation in the final examination in the Bologna system can vary depending on the particular institution, program, and country. In general, most institutions require students to have a minimum overall score of “Pass” to be eligible to take final exams. However, some institutions may have to change the minimum acceptable mark to be in line with the approved system and their examination policy. This research sheds light on the possibility of accepting extra students to participate in the final exam, if their scores are slightly less than the general admission score, and predicting their success based on the student’s grades in previous years. Different kinds of supervised machine learning regression analysis have been applied to give promising results when applied to previous actual records of students in the College of Engineering, in addition, to hundreds of random marks to increase the accuracy of estimating students' acceptance rate for final exams. This research will help weak grades students and allow them to participate in the final exam with the possibility of success.